The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpsyt.2023.1128406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of esketamine on postoperative depressive symptoms in patients undergoing thoracoscopic lung cancer surgery: A randomized controlled trial

Abstract: BackgroundDepressive symptoms are common among patients with lung cancer. We aimed to assess the effects of esketamine on postoperative depressive symptoms after thoracoscopic lung cancer surgery.MethodsIn this randomized, double-blind, placebo-controlled trial, 156 patients undergoing thoracoscopic lung cancer surgery were randomly allocated in a 1:1 ratio to receive intravenous esketamine (intraoperatively and in patient-controlled analgesia until 48 h postoperatively) or normal saline placebo. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Several previous studies addressed the controversial effects of ketamine on postoperative depression. In 2023, Gan et al [ 11 ] discussed the effect of esketamine on the occurrence of depressive symptoms in patients undergoing thoracoscopic lung cancer surgery. In that study, 156 patients received ketamine infusion during and 48 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies addressed the controversial effects of ketamine on postoperative depression. In 2023, Gan et al [ 11 ] discussed the effect of esketamine on the occurrence of depressive symptoms in patients undergoing thoracoscopic lung cancer surgery. In that study, 156 patients received ketamine infusion during and 48 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Normal saline was administered to the control group and Beck's questionnaire was used to evaluate results. They found that depressive symptoms decreased 1 month after the operation [ 11 ]. In 2023, Zhang et al [ 10 ] examined Crohn's patients undergoing intestinal resection treated with ketamine at a dose of 0.25 mg/kg as an intravenous drip and then with a dose of 0.12 mg/kg/hr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 Our recent work also suggested that a perioperative low-dose esketamine infusion reduced postoperative depressive symptoms in patients after thoracoscopic lung cancer surgery. 15 However, as far as we know, there is no study on perioperative use of esketamine in perimenopausal women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%